The first standard grammar of Malay; George Werndly’s 1736 Maleische spraakkunst - Mahdi, Waruno (Wacana, Journal of the Humanities of Indonesia, 2018)
A brief biography of George Henrik Werndly and description of contemporaneous development of linguistics is followed by a perusal of Melchior Leydekker’s and Petrus van der Vorm’s policy of strictly using Classical Malay in Christian publication, that served as basis of Werndly’s work. Then, a detailed perusal of Werndly’s 1736 Malay grammar, in particular the divisions (“books”) on (I) spelling, (II) morphology, and (III) syntax, is illustrated by reproductions of original text passages. Elements of the complicated Latin-script spelling are demonstrated in detail and compared with that of other authors in separate tables. Werndly’s grammatical terminology is considered, and where Arabisms are used, Werndly’s spelling is provided besides modern Indonesian cognates and Arabic etymons. Signs of a likely precolonial Malayan grammar tradition are inspected. Finally, the partly unexpected influence of Werndly’s work on language policy of the nineteenth and twentieth centuries is inspected.